ANALYSIS OF INDONESIA’S ISLAMIC BANKING BANKRUPTCY PREDICTION FOR PERIOD 2014-2016 - Anton Bawono; Aisyah Setyaningrum (Ekonomi Syariah IAIN Kudus, 2018)
The background of this study was based on market share of Isalmic banks in which it is only 5% of National Banks in Indonesia. This indicates ineffective Islamic banks performance. Therefore it will lead to the bankruptcy. Assessing bankruptcy required deep assessment of company performance through its financial ratios; these are Working Capital to Total Assets (WCTA), Earnings Before Interest and Tax to Total Assets (EBITTA), Retained Earnings to Total Assets (RETA) and Book Value of Equity to Book Value of Total Debt (BVEBVTD). The purpose of this study was intended to explain about the influence of those financial ratios on bankruptcy prediction of banks based on Altman Z-Score Model.The data was conducted through indirect observation from quarterly financial report of banks for period 2014-2016. The samples were 11 Sharia banks from 13 Sharia banks listed on Indonesia Financial Services Authority (OJK-RI) by January 2017. The process of analysis was started by conducting Stationery analysis then Regression analysis, the test of assumptions and Multiple Discriminant Analysis (MDA).The result suggests that WCTA, EBITTA and BVEBVTD variable show positive and significance effect on bankruptcy prediction, while the RETA variable shows negative and insignificance. Based on this study, there are only two variables, WCTA and BVEBVTD, that couldpredict bankruptcy with 98.2% accuracy.